What Drives Digital Payment Adoption? Examining the Role of Ease of Use, Security, and Trust - Riri Alifah Fakriah; Mohammad Dheo Alfhito; Mardiyani (Journal of Enterprise and Development)
Purpose: This research examines the factors affecting the adoption of digital payments, focusing on how perceived ease of use and perceived security impact this adoption, with user trust serving as a mediating variable. Method: Data were collected in Cirebon City through a survey conducted via Google Forms, distributed both online and offline. A total of 180 respondents participated in the study. The sampling technique employed was purposive sampling, targeting individuals who currently use or have used digital payments. The data were analyzed using structural equation modeling with the partial least squares (SEM-PLS) approach. Result: The study's findings indicate that both perceived ease of use and perceived security significantly influence user trust. Additionally, these factors also have a notable impact on the adoption of digital payments. User trust effectively mediates the relationship between perceived security and digital payment adoption. Practical Implications for Economic Growth and Development: This study highlight the importance for service providers to streamline digital transaction processes, enhance security measures, and offer transparent education on data protection to foster greater adoption of digital payments. The rise in digital payment usage not only enhances financial literacy but also promotes financial inclusion within society. This research offers valuable insights for the financial industry and regulators in developing policies that can bolster public trust in digital payment systems, ultimately contributing to a more advanced, inclusive, and sustainable digital economy in Indonesia.